Modified gastrostomy feeding tubes in patients with oesophageal cancer: our experience from Northern Tanzania. Issue 5 (27th May 2021) - Lodhia, Jay; Suleiman, Jamil; Chipongo, Hillary; Shadrack, Mathayo; Msuya, David; Chilonga, Kondo
Abstract: Surgeons in resource-limited settings have adapted to overcome the challenges of the limitations of resources using different available methods and inventions from the local environment. We report four cases of oesophageal cancer palliatively treated with improvised gastrostomy feeding tubes by using 24Fr urinary catheters, to optimize their nutritional status to withstand chemotherapy/radiotherapy. Two patients managed to begin chemo and radiotherapy, but only one out of the four survived. The aim of this report is to appraise the methods used by surgeons to overcome the challenges they face in clinical practice.